2023
DOI: 10.1021/acs.jctc.2c01143
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Structures and Conformational Landscapes of Amino Acids in the Gas Phase: A Joint Venture of Machine Learning, Quantum Chemistry, and Rotational Spectroscopy

Abstract: The accurate characterization of prototypical bricks of life can strongly benefit from the integration of high resolution spectroscopy and quantum mechanical computations. We have selected a number of representative amino acids (glycine, alanine, serine, cysteine, threonine, aspartic acid and asparagine) to validate a new computational setup rooted in quantum-chemical computations of increasing accuracy guided by machine learning tools. Together with low-lying energy minima, the barriers ruling their interconv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(79 citation statements)
references
References 119 publications
3
76
0
Order By: Relevance
“…Contrary to the usual situation for aliphatic amino acids, conformers of type II are more stable than their types I and I′ counterparts in spite of a less favorable orientation of the OH group in the carboxyl moiety. The increased stability of these conformers is related to the existence of a “daisy chain” sequence of interactions involving aromatic π electrons, together with the NH 2 and OH groups of the backbone .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrary to the usual situation for aliphatic amino acids, conformers of type II are more stable than their types I and I′ counterparts in spite of a less favorable orientation of the OH group in the carboxyl moiety. The increased stability of these conformers is related to the existence of a “daisy chain” sequence of interactions involving aromatic π electrons, together with the NH 2 and OH groups of the backbone .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, equilibrium rotational constants require very accurate geometrical parameters, which can be obtained only with state-of-the-art QC methods, although reasonable relative errors (typically 0.4–0.5%) are obtained at the rDSD level . We have recently shown that the systematic nature of the errors permits to improve significantly the rDSD geometrical parameters, and thus equilibrium rotational constants, by a linear regression approach (hereafter LRA). ,, In this model, the computed geometrical parameters ( r comp ) are corrected for systematic errors by means of scaling factors ( a ) and offset values ( b ) depending on the nature of the involved atoms and determined once for ever from a large database of accurate semiexperimental (SE) equilibrium geometries: ,, r L R A = a × r c o m p + b …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,17,23,24 From the theoretical side, many authors have been involved in the search for serine and protonated serine conformers. 14,[25][26][27][28][29][30][31][32][33][34] For neutral serine, we found the one published by He and Allen 25 to be the highest in terms of the level of theory and in the number of conformers found. They systematically mapped the conformational space with rotating the most flexible parts of the molecule, and performed geometry optimizations at the RHF/6-31G* level.…”
Section: Introductionmentioning
confidence: 99%